Comparison of efficiency and emission characteristics in a direct-injection compression ignition engine fuelled with iso-octane and methanol under low temperature combustion conditions. (15th April 2022) - Xu, Leilei; Treacy, Mark; Zhang, Yan; Aziz, Amir; Tuner, Martin; Bai, Xue-Song
Abstract: Gasoline and methanol are highly recommended for low temperature combustion (LTC) engines due to their high research octane number. However, engines fuelled with these fuels suffer from high unburned hydrocarbon (UHC) and carbon monoxide (CO) emissions at low loads, which can be improved by controlling the level of mixture stratification. This paper reports on the experimental and numerical comparison of the emission characteristics and engine performance of methanol and iso-octane in a heavy-duty direct-injection compression ignition engine operating in HCCI and PPC regimes. Overall, methanol requires a higher intake temperature, compared with iso-octane, to counter the high heat of vaporization. The onset of ignition is from the relatively fuel-lean regions resulting in lower CO emissions. This is due to the methanol ignition delay times being less sensitive to the fuel/air mixture and the larger temperature gradient of the equivalence ratio. Methanol achieves lower charge stratification because of its low stoichiometric A/F ratio, which extends the SOI window with ultra-low NO x emissions. However, methanol suffers from higher UHC emissions in the HCCI regime due to fuel trapped in the crevice region. Three cases include HCCI, PPC with low and high mixture stratification were detailed investigated. Of these cases, PPC with low mixture stratification case shows the highest engine thermal efficiency and the lowest emissions. Methanol has more advantages operating in the PPC regime in the aspect of emissions. Highlights: The overall trend of the intake temperature for both fuels shows 'spoon' shape. Methanol requires a higher intake temperature to counter the high heat of vaporization. Ignition of methanol is from the relatively fuel-lean regions resulting in lower CO emissions. Methanol achieves lower charge stratification because of its low stoichiometric A/F ratio. Methanol has more advantages operating in the PPC regime in the aspect of emissions.